Implementasi Metode Contextual Learning dalam Pembelajaran Aqidah Akhlak Siswa di MIN 1 Pesawaran - Nurmala Dewi; Anggi Septia Nugroho; Ahmad Luviadi (Permata : Jurnal Pendidikan Agama Islam, 2024)
Learning methods are steps chosen and used in implementing practical strategies to facilitate teachers and students in achieving learning objectives. Less interesting or inappropriate learning methods will cause several problems. Among them are students' lack of interest in learning, students' motivation in learning decreases, students find it difficult to understand the material and so on. Therefore, researchers want to conduct research related to how the implementation of Contextual Learning methods in overcoming some of the learning problems above. The purpose of this study was to determine the implementation of the Contextual Learning method in the teaching and learning process of Aqidah Akhlak class 6A at MIN 1 Pesawaran in the 2023/2024 learning year. Researchers used the Descriptive Qualitative approach method by involving several data sources, namely teachers and students. Data collection in this study used interview, observation and documentation techniques. The results of this study in applying the contextual learning method at MIN 1 Pesawaran use the following steps: Constructivism, Inquiry (finding), Questioning (asking), Learning Community (learning community), Modeling (modeling), Reflection (reflection), and Authentic Assessment (actual assessment).Keyword : Implementation Method; Contextual Learning; Aqidah Moral Lessons